Cs2 'diffuse bands' emission from superheated cesium vapor. (21st June 2016) - Pichler, G; Makdisi, Y; Kokaj, J; Thomas, N; Mathew, J; Beuc, R
Abstract: Thermal emission from superheated cesium vapor was studied to very high temperatures from 700 °C to 1000 °C. This was performed in the vapor condition only and with no liquid cesium present in the all-sapphire cell. We observed a number of atomic and molecular spectral features simultaneously in emission and absorption, especially peculiar thermal emission of cesium dimer diffuse bands (2 3 Πg → a 3 ∑u + transitions) around 710 nm coexisting with absorption bands around first resonance lines at 852 and 894 nm. We performed appropriate calculations of the diffuse band emission profiles and compared them with measured profiles. We also performed absorption measurements and compared observed diffuse band profiles with calculated ones. Possible applications of the observed phenomena will be discussed in terms of the solar energy conversion using dense cesium vapor.